Inflation illiteracy: A micro-data analysis - Fredrik N. G. Andersson; Erik Hjalmarsson; Pär Österholm (Örebro University School of Business, 2022)
Survey data indicate that a relatively large share of households is ill-informed about the rate of inflation in the economy, with perceived and expected rates of inflation deviating substantially from official measures. Using Swedish micro-level data, we find that such inflation illiteracy is related to respondent characteristics, including income, education and sex.
Keywords: E31; 330; Perceived inflation; Inflation expectations; Survey data; Economic literacy